1995
DOI: 10.1021/ja00127a037
|View full text |Cite
|
Sign up to set email alerts
|

An Estrogen-Nucleic Acid Adduct. Electroreductive Intermolecular Coupling of 3,4-Estrone-o-quinone and Adenine

Abstract: Estrogens have been shown to induce mammary, pituitary, cervical, and uterine tumors in rats, mice, and guinea pigs.1 Estradiol and other estrogens induce renal carcinoma in 80-100% of Syrian hamsters within 6-8 months.* 12 Although the exact mechanism for carcinogenesis induced by estrogenic compounds is not fully understood, it is generally believed that metabolic activation of estradiol leading to the formation of catechol estrogens is a prerequisite for its genotoxic activity.3 It has been proposed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…There are several main classes of electron transfer agents, some of them already mentioned: nitroaromatics (6, 8-10, 13-14) (or their reduced forms, 15), quinones (5, 11-12) (or phenolic precursors 21, 23, 24), aza compounds (or azo dyes), iminium ions [or imines, aromatic (25,26) and aliphatic N-oxides, triarylmethane dyes (27), Nheterocyclic salts (28)] and metal complexes (1, 29) or metal quelators. In the present case, emphasis will be held on nitroaromatics and quinones.…”
Section: Main Classes Of Compounds Biologically and Electrochemicallymentioning
confidence: 99%
“…There are several main classes of electron transfer agents, some of them already mentioned: nitroaromatics (6, 8-10, 13-14) (or their reduced forms, 15), quinones (5, 11-12) (or phenolic precursors 21, 23, 24), aza compounds (or azo dyes), iminium ions [or imines, aromatic (25,26) and aliphatic N-oxides, triarylmethane dyes (27), Nheterocyclic salts (28)] and metal complexes (1, 29) or metal quelators. In the present case, emphasis will be held on nitroaromatics and quinones.…”
Section: Main Classes Of Compounds Biologically and Electrochemicallymentioning
confidence: 99%
“…Earlier studies showed that, under electrochemical reductive conditions, 3,4‐E 1 Q in dimethylformamide (DMF) reacted to form an adduct with adenine (3,4‐E 1 Q‐1‐C 8 Ade) 20. This procedure, being cumbersome for large‐scale reactions, was replaced by a chemical reductive process involving sodium dithionite in dry DMF to generate the 3,4‐estrone semiquinone radical anion and finally to synthesise adducts with the nucleobases and deoxynucleosides 21,22.…”
Section: Protonated Molecules Of the Adducts Detected In The Reactionmentioning
confidence: 99%
“…The covalent binding of oestrogen quinone reactive intermediates to guanine and adenine nucleic acid bases has also been investigated in cell-free test systems and in rats and hamsters in vivo (Table 11) (Abul-Hajj et al, 1995;Stack et al, 1996;Cavalieri et al, 1997;Roy and Abul-Hajj, 1997;Shen et al, 1997Shen et al, , 1998. Quinone intermediates of 4hydroxylated oestrogens have been shown to form unstable DNA adducts, which decompose and form potentially mutagenic apurinic sites, whereas 2-hydroxylated oestrogen metabolites generate more stable DNA adducts .…”
Section: Genotoxicity Of Oestrogensmentioning
confidence: 99%